2016
DOI: 10.1557/mrs.2016.185
|View full text |Cite
|
Sign up to set email alerts
|

Computational modeling of the mechanics of hierarchical materials

Abstract: Structural hierarchy coupled with material heterogeneity is often identified in natural materials, from nano-to macroscale. It combines disparate mechanical properties, such as strength and toughness, and multifunctionality, such as smart adhesion, water repellence, self-cleaning, and self-healing. These architectures can be employed in synthetic bioinspired structured materials, also adopting constituents with superior mechanical properties, such as carbon nanotubes or graphene. Advanced computational modelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…In bio-inspired materials research new properties have been obtained by mimicking the structure observed in biological systems, suggesting that the key factor lies in the hierarchical architecture with interacting features at different size scales, whose combined effects lead to emergent synergistic properties 23 . This is true for friction of multi-structured surfaces, where intrinsic multiscale interactions can be combined with artificially introduced ones.…”
Section: Introductionmentioning
confidence: 99%
“…In bio-inspired materials research new properties have been obtained by mimicking the structure observed in biological systems, suggesting that the key factor lies in the hierarchical architecture with interacting features at different size scales, whose combined effects lead to emergent synergistic properties 23 . This is true for friction of multi-structured surfaces, where intrinsic multiscale interactions can be combined with artificially introduced ones.…”
Section: Introductionmentioning
confidence: 99%
“…Given the relative scarce variation in the basic constituent materials (essentially combinations of hard mineralized and soft tissues), the great variety of mechanical properties achieved in natural materials is mainly obtained through the complexity of structural architectures, including material arrangements, mixing, and grading over different size scales. The mechanical modelization of these complex, often hierarchical structures, requires advanced modelling tools, with the possibility of simultaneously including different length scales in simulations [131][132][133][134].…”
Section: Numerical Modelling Of Bio-inspired Structuresmentioning
confidence: 99%
“…Maiti et al [32] used coarse-grained molecular dynamics to study the behaviour of self-healing polymers and compute parameters such as the local elastic modulus, reaction rates and cure kinetics, for a continuum macroscopic scale model. A review of early attempts of applying numerical methods to self-healing materials is given in [33], and a more recent review on computational modelling of hierarchical materials, including self-healing, is provided in [34].…”
Section: Introductionmentioning
confidence: 99%